Effect of R119G Mutation on Human P5CR1 Dynamic Property and Enzymatic Activity. (18th January 2017) - Li, Linhua; Ye, Yujia; Sang, Peng; Yin, Yirui; Hu, Wei; Wang, Jing; Zhang, Chao; Li, Deyun; Wan, Wen; Li, Rui; Li, Longjun; Ma, Linling; et al.
Abstract : Pyrroline-5-carboxylate reductase (P5CR1) is a universal housekeeping enzyme that catalyzes the reduction of Δ1-pyrroline-5-carboxylate (P5C) to proline with concomitant oxidation of NAD(P)H to NAD(P) + . The enzymatic cycle between P5C and proline is important for function in amino acid metabolism, apoptosis, and intracellular redox potential balance in mitochondria. Autosomal recessive cutis laxa (ARCL) results from a mutation in P5CR1 encoded by PYCR1. Specifically, the R119G mutation is reported to be linked to ARCL although it has not yet been characterized. We synthesized R119G P5CR1 and compared it to WT P5CR1. Foldx prediction of WT and R119G mutant P5CR1 protein stability suggests that the R119G mutation could significantly reduce protein stability. We also performed enzymatic activity assays to determine how the mutation impacts P5CR1 enzymatic function. The results of these experiments show that mutagenesis of R119 to G decreases P5CR1 catalytic efficiency for 3, 4-dehydro-L-proline relative to WT. Mutagenesis and kinetic studies reveal that the activity of the mutant decreases as temperature increases from 5°C to 37°C, with almost no activity at 37°C, indicating that this mutation impairs P5CR1 function in vivo. Conversely, WT P5CR1 retains its activity after incubation at 37°C and has essentially no remaining activity at 75°C. Taken together, our experimental results indicate the R119G mutation could be an involving pathomechanism for ARCL.